End of life care in Wales: evaluation of a care pathway-based implementation strategy. Issue 2 (1st June 2012) - Johnstone, Rosalynde Patricia; Jones, Angela; Fowell, Andrew; Burton, Christopher Richard; Rycroft-Malone, Jo
Abstract : Objectives: The All Wales Care Pathway for the End of Life Pathway aims to ensure evidence-based end-of-life care is available across Wales. Implementation of end-of-life care processes was evaluated in a national audit of deaths between July 2007 and June 2009. Methods: Up to 60 records of deceased patients were reviewed by two researchers from hospital (24), community localities (20), hospice and specialist inpatient (9) settings. Data extraction using a standard template was carried out at all sites to indicate whether end-of-life care processes had been implemented. A total of 1184 records were retrieved. 202 records were excluded due to sudden death (eg, cardiac arrest) or incomplete data. Sampling included 580 decedents (59%) who had received end-of-life care through the pathway. Results: Pathway use was associated with improved implementation of all evidence-based clinical standards other than for daily review, where implementation was consistently high with (84.5%) or without the pathway (81%). Differences in achievement were most evident for the implementation of bereavement and spiritual support where the pathway was used. Implementation within hospice and specialist inpatient care settings was consistently high. Conclusion: Integrated care pathway use is associated with the implementation of best practice in end-of-life care. However, variation in implementation across sites and the influence of setting type highlights the mediating effect of organisational context which, together with different methods of feedback, may provide a useful agenda for implementation research within end-of-life care.